Produção da microalga Nannochloropsis oculata e seu uso como aditivo na ração do camarão Litopenaeus vannamei - Bezerra, João Henrique Cavalcante (2020)
With the stagnation of fishing activities, aquaculture has become the world's main source of fish, due to its accelerated growth in recent decades. Shrimp farming is the productive sector dedicated to the cultivation crustaceans, with emphasis on Litopenaeus vannamei, which had a reduction in production rates in several countries, mainly due to problems related to diseases, being necessary to seek alternatives to increase the immune system of this species. The objective of the present work was to evaluate the immunostimulating effect of the microalgae Nannochloropsis oculata in the cultivation of Litopenaeus vannamei, as well as to evaluate and compare the growth and the lipid yield of the microalgae N. oculata in Guillard f / 2 medium with different concentrations of sodium nitrate, evaluate the growth in alternative culture medium based on urea and triple superphosphate (SPT) and the zootechnical parameters of the shrimp. Three subsequent experiments were carried out. In the first, the cultivation of microalgae N. oculata was carried out in Guillard f / 2 medium in a volume of three liters, differentiating the concentrations of sodium nitrate (15, 30, 45, 60 and 75 mg L-1) under the conditions of 60 μmol cm-2 s-1 of light intensity, 28 ± 1 ° C of temperature and salinity 30. In the second experiment, the same microalgae was cultivated in three treatments, two in Guillard f / 2 medium in the concentrations of sodium nitrate (15 and 75 mg L-1) and one with an alternative culture medium based on urea and SPT. All three treatments were carried out in a volume of 20L under the same conditions of the previous experiment. Finally, four diets were tested in the shrimp culture. The first diet consisted only of commercial feed with 35% CP as a control treatment. In treatment 1, the algal biomass obtained in the Guilard f / 2 medium with 75 mg L-1 was used. In treatment 2, the algal biomass obtained in the Guilard f / 2 medium with 15 mg L-1 of sodium nitrate was used and in treatment 3, the algal biomass obtained in the cultivation carried out in the alternative medium was used. In all treatments, the algal biomass content as an additive was 5% of the amount of feed offered. The results showed that the amount of hemocytes was drastically reduced over the days of cultivation. However, among the treatments observed, shrimp fed with microalgal biomass grown in Guillard medium containing 15 mg L-1 of sodium nitrate, contained a greater amount of hemocytes. When N. oculata was submitted to different concentrations of nitrate, the best results of maximum cell density and specific growth rate occurred in the concentration of 75 mg L-1 of sodium nitrate in Guillard f / 2, however, the lipid yield was inversely proportional to the increase in nitrate concentration. The highest lipid yield occurred with 15 mg L-1 of sodium nitrate present in the Guillard f / 2 medium, and the results in cultivation in an alternative medium showed a higher maximum cell density, higher specific growth rate and, consequently, shorter time of crops generation.